Do medical residents perform patient-centered medical home tasks? A mixed-methods study. Issue 1 (1st January 2017) - Block, Lauren; LaVine, Nancy; Verbsky, Jennifer; Sagar, Ankita; Smith, Miriam A.; Lane, Susan; Conigliaro, Joseph; Chaudhry, Saima A.
ABSTRACT: Background : Increasingly, residents are being trained in Patient-centered Medical Home (PCMH) settings. A set of PCMH entrustable professional activities (EPAs) for residents has been defined but not evaluated in practice. Objective : To understand whether residents trained at PCMH sites reported higher likelihood of engaging in PCMH tasks than those training in non-PCMH sites. Design : Survey and nominal group data from post-graduate trainees at three residency programs. Results : A total of 179 residents responded (80% response). Over half (52%) cared for patients at PCMH sites. Residents at PCMH sites were more likely to report engaging in tasks in the NCQA domains of enhancing access and continuity (p < 0.01 for 4/11 tasks), planning and managing care (p < 0.01 for 3/4 tasks), providing self-care and community support (p < 0.01 for 3/5 tasks), and identifying and managing patient populations (p < 0.01 for 1/6 tasks), but were not more likely to report tracking and coordinating care or measuring and improving performance. Residents at PCMH sites were more likely to report working with medical assistants (p < 0.01), but not other healthcare professionals. Qualitative data showed staff teamwork and continuity of care as facilitators of patient-centered care, and technological problems and office inefficiencies as barriers to care. Conclusions : Residents trained at PCMH sites were more likely to engage in tasks in several NCQA domains, but not care coordination and quality assessment. Similar facilitators and barriers to trainee provision of patient-centered care were cited regardless of PCMH status. Curricula on PCMH principles and workflows that foster continuity and communication may help to inform residents on PCMH tenets and incorporate residents into team-based care. Abbreviations : EPA: Entrustable professional activity; GIM: General Internal Medicine; NCQA: National Center for Quality Assurance; PCMH: Patient-centered medical home